2015
DOI: 10.1007/s00702-015-1482-5
|View full text |Cite
|
Sign up to set email alerts
|

Electronic media use and insomnia complaints in German adolescents: gender differences in use patterns and sleep problems

Abstract: Electronic media play an important role in the everyday lives of children and adolescents and have been shown to be associated with sleep problems. The objective of this study was to assess the associations between time spent using different electronic media and insomnia complaints (IC) in German adolescents with particular respect to gender differences in use patterns and associations with IC. Cross-sectional data of a weighted total of 7533 adolescents aged 11-17 stem from the German Health Interview and Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 50 publications
3
29
0
3
Order By: Relevance
“…Thus, online activity on SNS exceeds the planned time, which causes increased exposure to light emitted from mobile devices. The light emitted from mobile devices can interfere with the circadian rhythm and decrease melatonin secretion, causing an individual to have sleeping difficulties, which could lead to sleep deprivation and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, online activity on SNS exceeds the planned time, which causes increased exposure to light emitted from mobile devices. The light emitted from mobile devices can interfere with the circadian rhythm and decrease melatonin secretion, causing an individual to have sleeping difficulties, which could lead to sleep deprivation and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic devices like smartphones and PCs are used for extensive time periods every day, both in school and during leisure time [29]. It has been hypothesized that there is an association between excessive use (> 4 hours a day) of electronic devices and the presence of headache and insomnia [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported significant gender differences in social media use among adolescents and adults (Smith & Anderson, 2018), and that females display more intense use than males in general (Frison & Eggermont, 2016;McAndrew & Jeong, 2012), yet other studies noted no gender difference for social media use among adults (Bhat et al, 2018). Significant gender differences are documented in terms of sleep as well (Mallampalli & Carter, 2014) and the association between different types of electronic media use and sleep complaints have been shown to differ for adolescent boys and girls (Lange et al, 2017). Both social media use and sleep (Ohayon, Carskadon, Guilleminault, & Vitiello, 2004;Smith & Anderson, 2018) are strongly related to age and age also significantly moderated the relationship between bedtime mobile phone use, sleep duration and fatigue among adults (Exelmans & Van den Bulck, 2016b).…”
Section: Introductionmentioning
confidence: 99%